Sensory evaluation of caprine yogurt added with pulpes of mandacaru and yellow passion (Research, Society and Development, 2020)
Yogurt is considered a good source of protein, calcium, riboflavin and vitamin B12, which has beneficial effects for humans. Given the above, the aim of this study was to prepare a prebiotic goat yogurt, added with passion fruit jelly (Passiflora edulis), and mandacaru pulp (Cereus jamacaru) and evaluate sensory parameters. For this, 2 formulations of goat yoghurt were developed: IC (Yogurt Caprino Controle), added from the starter culture Streptococcus salivarius subsp. thermophillus and Lactobacillus delbrueckii subsp. Bulgaricus and IPREB (Yogurt Caprino Prebiótico) added prebiotic fiber oligofructose (FOS), in addition to the starter culture, all yoghurts added with 15% jelly. Yogurt processing was carried out in triplicates and analyzed at times 1, 7, 14, 21 and 28 days of cold storage (4 ± 1 ° C). It can be observed, from the results found that there was no statistical difference (p> 0.05) between the formulations, regarding the attributes appearance, color, aroma, flavor, consistency and overall assessment. In general, it can be observed that all the sensory parameters, the formulations were well accepted, since the grades varied between the hedonic terms "I liked it moderately" (note = 7) to "I liked it very much" (note = 8). Thus, it is clear that the development of prebiotic goat yogurt with mandacaru and passion fruit jelly has great commercialization potential, adding attractive functional and sensory characteristics in the same product.